Gestión de ventas del Almacén Don Pato de la ciudad de Babahoyo - Espinoza Gonzabay, Mayra Rocio (2021)
At the time that the health problem of Covid 19 appeared, Don Pato warehouse took new strategies to ensure that its products are sold and thus not lose its customers, since in the virtual mode there were more competitors who sold products of The ones that the store promoted, the store changed the way of selling to improve the stability of its business with the sole purpose of achieving favorable results, and thus perfecting and transmitting security and reliability, for this research the Qualitative methodology was used that helped to understand the social phenomenon and its characteristics, Quantitative that defines what was the objective to which it is desired to address, that is, current clients such as men and women of all ages, the documentary research that will help us identify the problem that exists with secondary data, that is, in the books that allows us to draw conclusions, and we also use the surveys that are I do it to consumers in order to obtain more relevant information on the subject in question to obtain necessary and precise information to be able to determine the factors that are presented in the Don Pato store, among which are the needs, satisfaction and with the objective that will determine the new sales efforts.